CHRONOTOPE IN UZBEK LITERATURE ON THE EXAMPLE OF WORKS OF CLASSICAL AND MODERN AUTHORS - Makhmadieva Gulchekhra Sait-Abdullaevna (Modern American Journals, 2025)
The article is devoted to the study of chronotope in Uzbek literature on the example of works of classical and modern authors. The specificity of spatio-temporal models, such as mahalla, bazaar, caravan route, factory and psychological spaces, is revealed. The analysis emphasizes that in classical literature the chronotope of traditional community and historical memory dominates, while in post-Soviet prose the role of individualized and mythopoetic prose is strengthened Spaces. It is shown that the chronotope in Uzbek literature reflects the processes of cultural transformation, the formation of national identity and internal changes in the perception of time and space.
Keywords: Chronotope, Uzbek literature, spatio-temporal models, mahalla, bazaar, caravan route, psychological space, historical time, national identity, post-Soviet prose.